A theological analysis of the concept of the future's openness in African religious discourse - Jaba, Mogomotsi (KAMASEAN: Jurnal Teologi Kristen, 2024)
Ongoing theological discussions persist within evangelical Christian theological circles regarding the question of whether the future is predetermined by God or not. Classical theists assert that God has unequivocally predetermined the future. In this particular arrangement, although the future may be unknown to humans, it already exists and is known by God. According to Classical theists, all moments in time, including the future, exist simultaneously before God. On the other hand, there are Open theists who explicitly reject this deterministic perspective. Open theists believe that the future is yet undetermined and is still in the process of becoming. This article sought to achieve two interconnected theological manoeuvres. Firstly, it aimed to broaden the discussions regarding the nature of the future inside African religious discourse. Secondly, the article aimed to justify the belief that the future is unknown to both God and mankind based on African religious reflection. This task was conducted using analytic theology as a research method. The conclusion drawn is that in African religious thought, the future is perceived as non-existent at present. The article contributes to the field of multicultural theology.